2010
DOI: 10.1111/j.1440-1584.2010.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of occupational stress in the remote area nursing workforce

Abstract: In a context of high stress, high levels of work engagement and moderate levels of job satisfaction do not obviate high workforce turnover for this population. There is a need to reduce job demands and increase job resources in order to foster long-term work engagement and reduced emotional exhaustion. This might subsequently decrease remote area nursing workforce turnover.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 23 publications
2
61
0
1
Order By: Relevance
“…Results of RAHW focus group research [39] support this finding. The inability to meet high clinical demand has been associated with emotional exhaustion in remote area nurses [40]. Lenthall et al, (2009) suggest that this situation is “exacerbated by a low-resource environment” [41] but results of this study did not identify resources as a significant contributor to retention for either allied health cohort.…”
Section: Discussionmentioning
confidence: 62%
“…Results of RAHW focus group research [39] support this finding. The inability to meet high clinical demand has been associated with emotional exhaustion in remote area nurses [40]. Lenthall et al, (2009) suggest that this situation is “exacerbated by a low-resource environment” [41] but results of this study did not identify resources as a significant contributor to retention for either allied health cohort.…”
Section: Discussionmentioning
confidence: 62%
“…Mentally demanding jobs with low levels of control and/or less supportive environments are detrimental to health [4]. Several nursing studies have identified that diminished control over workplace decisions results in elevated occupational stress levels [9,28]. Furthermore, this theoretical framework was used to guide data analysis and interpret findings.…”
Section: Materials and Methods Designmentioning
confidence: 99%
“…Rural and northern areas of most northern countries have a severe shortage of health care professionals, including nurses. Those working in these regions face higher workloads, must work with less resources and have fewer opportunities for career and educational advancement [28,62]. Exacerbating the situation is that rural and northern residents are, on average, sicker [63] and have to travel greater distances to receive services, including health services, compared to residents in Southern Ontario.…”
Section: Occupational Stress and Quality Of Work Life O R I G I N A Lmentioning
confidence: 99%
“…[46] Similarly, some of the nurses indicated that cross-training was a source of stress and increased their professional clinical responsibility to the College of Nurses of Ontario (regulatory body in the province of Ontario, Canada). Indeed, given the already elevated workloads [47] that nurses experience, cross-training may place an additional burden on nurses' health and wellbeing.…”
mentioning
confidence: 99%